1999
DOI: 10.1002/(sici)1521-4141(199905)29:05<1667::aid-immu1667>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Self glycolipids as T-cell autoantigens

Abstract: Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system characterized by discrete areas of demyelination. An autoimmune response against components of myelin is thought to contribute to disease pathogenesis. Here we identify glycolipids as new targets recognized by T cells in multiple sclerosis patients. Circulating T cells reactive with glycolipids are more frequent in MS patients than in control donors as shown by enzyme-linked immunospot assay. They specifically recognize dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
188
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 253 publications
(196 citation statements)
references
References 30 publications
5
188
0
Order By: Relevance
“…We previously reported that both wild-type and soluble mCD1d1 assemble with PI and PI-glycans in vivo (11,12). However, in vitro, CD1 appears to bind a wide variety of lipids that vary in the chemical character of the moiety that directly interacts with the antigen-binding groove (11,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Therefore, our previous findings (11,12) may have been biased by the techniques used for the extraction, purification, and analyses of mCD1d1-associated ligands.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…We previously reported that both wild-type and soluble mCD1d1 assemble with PI and PI-glycans in vivo (11,12). However, in vitro, CD1 appears to bind a wide variety of lipids that vary in the chemical character of the moiety that directly interacts with the antigen-binding groove (11,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Therefore, our previous findings (11,12) may have been biased by the techniques used for the extraction, purification, and analyses of mCD1d1-associated ligands.…”
Section: Resultsmentioning
confidence: 96%
“…These lipids include cellular phospholipids and sphingolipids as well as mycobacterial phospholipids and mycolates (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Remarkably, however, CD1 molecules appear to associate with a restricted variety of lipids in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that DN T cells from SLE patients are restricted by CD1c raises the possibility that a nonpeptide self-Ag is presented to T cells. We hypothesize that cardiolipin and other self-glycolipids are ligands for CD1c-directly reactive T cells given the prominence of anticardiolipin Abs in SLE, the presence of CL in plasma lipoproteins (39), their structural similarity (polar head group with lipid tail) with other CD1-restricted T cell ligands (9,(11)(12)(13)(14)(15)37), and the recent report of T cell recognition of self-glycolipids (40).…”
Section: Discussionmentioning
confidence: 99%
“…CD1 proteins present a variety of pathogen-derived lipids to T cells in vitro (1)(2)(3)(4)(5)(6), and T cells reactive to mycobacterial lipid Ags have been isolated from the bloodstream of tuberculosis patients, providing evidence that CD1 and lipid-reactive T cells normally function in the host response during infections with Mycobacterium tuberculosis (7)(8)(9). However, CD1-mediated T cell responses are not limited only to foreign pathogens, as endogenous mammalian phosphatidylinositols normally bind to cellular CD1 proteins as they traverse the secretory pathway (10,11), and self gangliosides, phosphatidylinositols, sulfatides, and isoglobosides activate CD1-restricted T cells (12)(13)(14)(15)(16). Thus, mammalian APCs normally encounter and present both foreign and self lipid Ags to T cells, raising basic questions about how such responses are regulated.…”
mentioning
confidence: 99%